Problematika Gender di Suatu Perusahaan Dalam Lingkup Profesi Akuntansi - Destika Naya; Ucik Hidayati; Wella Putri Dea Rahmadani; Shamilatus Zakia; Nabila Rosidah; Mohammad Ali (PUTRA JAWA PUBLISHER, 2023)
When preparing and reviewing a company's annual financial statements, it is crucial to engage an accountant who considers materiality and the risk of inaccuracy. The decision-making process is influenced by various factors, including performance expectations, task complexity, and gender-related aspects of masculinity and femininity. The pressure to adhere to regulations impacts accountants' work, involving inappropriate directives from supervisors and the intricate nature of their tasks, leading to potential dysfunction. Feminine qualities come into play when navigating the pressure to comply and the complexity of the auditing task. Women may exhibit qualities such as order-taking, precision, and emotional control, resulting in a more cautious and risk-averse approach to the review process. This article aims to elucidate how accountants can enhance their consideration of their professional roles.